Effects of Underwriting and Claims Management on Performance of Property and Casualty Insurance Companies in East Africa - Angima, Caren B.; Mwangi, Mirie (European Scientific Journal, ESJ, 2017)
The insurance sector plays an important role in service economy of any country by underwriting of risks inherent in most sectors thus providing a sense of peace to most economic entities. Performance of general insurance companies is expected to be related to various factors, including optimal underwriting and prompt and efficient claims management functions. This study investigated the effect of underwriting and claims management practices on the performance of general insurance firms in East Africa. The study employed multiple linear regression analysis using primary and secondary data collected from 82 general insurers in Kenya, Uganda and Tanzania. The findings show that there is a significant positive relationship between underwriting and claims management practices employed by the firms and non-financial performance, but the relationship with financial performance was insignificant. The implication is that a profit oriented insurance firm should embrace a claims function that is closely related with the underwriting and pricing of the firm’s portfolio for meaningful results. It is recommended that general insurance companies focus on other important factors besides underwriting and claims management order to improve overall financial performance.